Associations of adiponectin with individual European ancestry in African Americans: the Jackson Heart Study - Bidulescu, Aurelian; Choudhry, Shweta; Musani, Solomon K.; Buxbaum, Sarah G.; Liu, Jiankang; Rotimi, Charles N.; Wilson, James G.; Taylor, Herman A.; Gibbons, Gary H. (Frontiers in Genetics, 2014)
Background: Compared with European Americans, African Americans (AA) exhibit lower levels of the cardio-metabolically protective adiponectin even after accounting for adiposity measures. Because few studies have examined in AA the association between adiponectin and genetic admixture, a dense panel of ancestry informative markers (AIMs) was used to estimate the individual proportions of European ancestry (PEA) for the African Americans enrolled in a large community-based cohort, the Jackson Heart Study (JHS). We tested the hypothesis that plasma adiponectin and PEA are directly associated and assessed the interaction with a series of cardio-metabolic risk factors. Methods: Plasma specimens from 1,439 JHS participants were analyzed by ELISA for adiponectin levels. Using pseudo-ancestral population genotype data from the HapMap Consortium, PEA was estimated with a panel of up to 1,447 genome-wide preselected AIMs by a maximum likelihood approach. Interaction assessment, stepwise linear and cubic multivariable-adjusted regression models were used to analyze the cross-sectional association between adiponectin and PEA. Results: Among the study participants (62% women; mean age 48 ± 12 years), the median (interquartile range) of PEA was 15.8 (9.3)%. Body mass index (p = 0.04) and insulin resistance (p = 0.0001) modified the association between adiponectin and PEA. Adiponectin was directly and linearly associated with PEA (β = 0.62 ± 0.28, p = 0.03) among non-obese (n = 673) and insulin sensitive participants (n = 1,141; β = 0.74 ± 0.23, p = 0.001), but not among those obese or with insulin resistance. No threshold effect was detected for non-obese participants. Conclusions: In a large African American population, the individual proportion of European ancestry was linearly and directly associated with plasma adiponectin among non-obese and non insulin-resistant participants, pointing to the interaction of genetic and metabolic factors influencing adiponectin levels.